Critical analysis of root : shoot ratios in terrestrial biomes - KAREL MOKANY; R. JOHN RAISON; ANATOLY S. PROKUSHKIN (Global Change Biology, 2006)
One of the most common descriptors of the relationship between root and shoot biomass is the root : shoot ratio, which has become a core method for estimating root biomass from the more easily measured shoot biomass. Previous reviews have examined root : shoot ratio data, but have only considered particular vegetation types and have not always critically reviewed the data used. Reliable root : shoot ratios are needed for a wide range of vegetation types in order to improve the accuracy of root biomass estimates, including those required for estimating the effects of land management and land use change in National Greenhouse Gas Inventories. This study reviewed root : shoot ratios in terrestrial biomes. A key facet of our analysis was a critical methodological review, through which unreliable data were identified and omitted on the basis of specific criteria. Of the 786 root : shoot ratio observations collated, 62% were omitted because of inadequate or unverifiable root sampling methods. When only the reliable data were examined, root : shoot ratios were found to be negatively related to shoot biomass, mean annual precipitation, mean annual temperature, forest stand age, and forest stand height. Although a single allometric equation derived in this study reliably predicted root biomass from shoot biomass for forests and woodlands, in general, the use of vegetation‐specific root : shoot ratios were found to be a more accurate method for predicting root biomass. When the root : shoot ratio data collated here were applied to an analysis of the global carbon budget, there was a 50% increase in estimated global root carbon stock, and a 12% increase in estimated total carbon stock of terrestrial vegetation. The use of the vegetation‐specific root : shoot ratios presented in this study is likely to substantially improve the accuracy of root biomass estimates for purposes such as carbon accounting and for studies of ecosystem dynamics.